2003
DOI: 10.1271/bbb.67.2674
|View full text |Cite
|
Sign up to set email alerts
|

A Transient RNA Interference Assay System UsingArabidopsisProtoplasts

Abstract: Double-stranded RNA (dsRNA) induces sequence-specific gene silencing in eukaryotes through a process known as RNA interference (RNAi). RNAi is now used as a powerful tool for functional genomics in many eukaryotes, including plants. We herein report a dsRNA-mediated transient RNAi assay system using protoplasts from Arabidopsis mesophyll cells and suspension-cultured cells (cell line T87). Introduction of dsRNA into protoplasts led to marked silencing of target transgenes. Our assay system would provide a conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…We have been attempting to develop a simple and effective system for inducing RNAi in plant cells, and recently reported that introduction of in vitro-prepared dsRNA into Arabidopsis protoplasts with polyethylene glycol (PEG) caused effective and specific interference with transgene activity. 4) Although this method has the potential to knock down endogenous genes, its applicability to endogenous genes has not been proved. Here we show that introduction of in vitro-prepared dsRNA into Arabidopsis T87 protoplasts also leads to marked silencing of endogenous genes.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…We have been attempting to develop a simple and effective system for inducing RNAi in plant cells, and recently reported that introduction of in vitro-prepared dsRNA into Arabidopsis protoplasts with polyethylene glycol (PEG) caused effective and specific interference with transgene activity. 4) Although this method has the potential to knock down endogenous genes, its applicability to endogenous genes has not been proved. Here we show that introduction of in vitro-prepared dsRNA into Arabidopsis T87 protoplasts also leads to marked silencing of endogenous genes.…”
mentioning
confidence: 99%
“…Comparison of their C T values indicated that their relative expression levels to Actin2/8 (internal standard, see below) were 0.1-2.1 for PAT1, 0.3-4.0 for sdh2-1, and 0.1-2.1 for sdh2-2 (n ¼ 3; expression of sdh2-3 was not detected, see below), confirming that they are surely expressed in T87 protoplasts except for sdh2-3. dsRNAs were prepared as described previously, 4) except that the T7 RiboMAX Express RNAi System (Promega, Madison, U.S.A.) was used for in vitro transcription. The sequence of the sGFP(S65T) gene (GFP) was used as a negative control.…”
mentioning
confidence: 99%
See 3 more Smart Citations